A DFT Study of Single‐Atom Catalysis of CO Oxidation Using Carbon‐Embedded Hexagonal Boron Nitride Monolayer. Issue 25 (6th July 2018) - Esrafili, Mehdi D.; Rad, Farzad Arjomandi
Abstract: The catalytic oxidation of CO by O2 molecule under mild conditions is one of the attractive processes in chemistry and industry. In the present study, by means of periodic density functional theory calculations, the potential of experimentally available carbon‐doped hexagonal boron nitride ( h ‐BN) nanosheets as a metal‐free catalyst for the CO oxidation is investigated. It is found that C‐doping induces high spin density into BN monolayer which is mainly localized over the C and its neighboring N or B atoms. Both Langmuir–Hinshelwood (LH) and Eley–Rideal (ER) mechanisms are considered for the CO oxidation reaction. The calculated reaction barriers reveal that the CO oxidation proceeds first via the LH mechanism CO + O2 → OCOO → CO2 + O* and then via the ER mechanism CO + O* → OCO* → CO2 . Our results suggest that the CO oxidation catalyzed by the C‐doped h ‐BN sheets is likely to occur at the normal condition. Abstract : Using the density functional theory, catalytic oxidation of CO by O2 molecule under mild conditions is studied carbon‐dopbed boron‐nitride nanosheets ( h ‐BN). Both Langmuir–Hinshelwood (LH) and Eley–Rideal (ER) mechanisms are considered for the CO oxidation reaction. The CO oxidation reaction over these surfaces can be characterized as a two‐step process. According to our results, the CO oxidation catalyzed by the C‐doped h ‐BN sheets is likely to occur at the normal condition.